Modification of Alginate Controlled-Release Formulations of Alachlor and Diuron with Pectin: Their Release Kinetics and Efficacy - Basari, Sopiah (2003)
Controlled-release formulation (CRF) of alachlor and diuron were prepared by a monolithic system using low methylester pectin and high methylester pectin as the polymers for the purpose of improving the initial release of active ingredient (a.i.) from the formulations. The release rates for both herbicides were evaluated by chemical assay and bioassay. Chemical assay using high performance liquid chromatography with ultraviolet detector showed the pectin-kaolin CRFs (PIKl, P2Kl, PIK and P2K) release a.i. was faster compared with alginate:pectin-kaolin CRFs (APIKl, AP2Kl, APIK and AP2K) and alginate-kaolin CRFs (AKI and AK2), six hours after placement in water. The release reached a constant level at three, five and seven days after placement in water for pectin-kaolin, alginate:pectin-kaolin and alginate-kaolin CRFs, respectively. The determination of release rate by bioassay technique was conducted in the glasshouse using Cucumis sativus and Brassica juncea seedlings as bioindicators for alachlor and diuron, respectively. At 3 days, after treatment (DAT), the CRF of alachlor (APIKl, AP2Kl, PIKI and P2Kl) showed a better performance in inhibiting shoot and root length of C. sativus compared to AKI. Similar result was observed for fresh weight of C. sativus at 15 DAT. The APIKl, AP2Kl, PIKI and P2Kl also showed a similar performance with the conventional spray formulation of alachlor (CFl) at the initial treatments. These indicated that the presence of pectin in the CRF improved the initial release of alachlor. At 160, DAT, all the CRFs showed a better effect compared to CFl indicating the prolonged activity of alachlor through the CRF. Similar results was observed for the CRFs of diuron in inhibiting germination of B. juncea. At 7 DAT, the pectin-koalin CRF (PIK and P2K) showed similar performance with the conventional spray formulation of diuron (CF) and significantly higher mortality was recorded from the CRFs of diuron compared to CF at 120 and 160 DAT.